Conflicts of Beliefs and Conflicts of Desires in the Technological Age. Historical Future and Social Disconsiderations Through the Case Study of Years And Years Series - Manzanero, Delia; Pallarès Piquer, Marc; Hernández Albarracín, Juan Diego; Villalobos Antúnez, José Vicente (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2021)
This paper elaborates a reflection on the power of audiovisual production in the interpretations of the political, social and existential crises of our present time. For this, a hermeneutical work is done on the British television miniseries Years and Years created and written by Russel T. Davies for BBC and HBO, concentrating on the narrative breadth it contains to critically think about phenomena such as the end of history, the post-politics and transhumanism, thus hovering over the complexity of the technological age. A work that integrates the analytics of a dystopian future that extends in its fictional virtuality beyond entertainment on the unthinkable and closer to a reality to come.